Aneurysmal Bone Cyst and Pregnancy: Is There Any Association? - Ravishankar S. Goel; Devendra Purohit; Jitendra Sekhawat; R. S. Mittal (Indian Journal of Neurosurgery)
Abstract Aneurysmal bone cyst (ABC) is an expansile, osteolytic lesion. The association of ABC with pregnancy is a very rare entity. We are reporting a unique case of spinal ABC, presenting as pathological fracture, paraplegia, and abdominal mass in the 28th week of pregnancy. A brief review of the literature is discussed. Dyshomeostasis of bone calcium, hormonal, and mechanical stress can aggravate the severity of ABC during pregnancy. A multidisciplinary approach is required to manage such cases, depending on the fetal gestational age and maternal neurological features.